Organisational Communication from the Bi-dimensional Perspective Management-Leadership: Defining Aspects, Confluences, and Peculiarities - Livia DURAC (Communications of International Proceedings, 2022)
This article analyses, from a theoretical perspective, the relevant aspects through which leadership can be differentiated from management, in an attempt to stress the importance of these differences. Starting from the purpose of the organisation, the way in which employees relate to the institutional entity where they cultivate and consolidate their professional values, approaching the main dimensions that structure organisational culture with an accent on communication, are the main objectives for the beginning of this paper. Certain terminological and content-related distinctions, translated through the tendency – somewhat frequently met – for common language to use the notions of management and leadership interchangeably, justify the part of the article treating this issue. Through its undeniable power to support and maintain inter-human relationships, communication is the resort where management and leadership meet, under the aspect of specific communication styles, as well as that of other components approached in the corresponding section.
Keywords: communication styles; organisation; leadership; management